Recent advances in tumor immunotherapy based on NK cells - Chen, Mengmeng; Zhang, Bing; Mu, Xuanlin; Zhang, Bingqiang; Yang, Tielin; Zhang, Gaofeng; Gu, Yuchao; Pei, Bin; Liang, Shaoshuai (Frontiers in Immunology, 2025)
Immunotherapy has emerged as the established fourth pillar of cancer treatment following surgery, radiotherapy, and chemotherapy, representing a cutting-edge research domain in translational medicine and clinical oncology. Natural killer (NK) cells, a type of innate cytotoxic lymphocyte, possess unique antitumor properties that are independent of major histocompatibility complex (MHC) restrictions, making them promising candidates for “off-the-shelf” therapeutic products. NK cells can eliminate tumor cells through various mechanisms. Genetic engineering of NK cells can enhance their activation signals, promote proliferation, inhibit suppressive signals, and improve tumor homing, all of which are expected to significantly boost their clinical efficacy. Compared to chimeric antigen receptor T (CAR-T) cell therapy, NK cell-based immunotherapy demonstrates superior safety and tolerability. However, the clinical application of NK cells still faces several challenges, including suboptimal expansion efficiency in vitro, limited persistence in vivo, low transduction efficiency of chimeric antigen receptor NK (CAR-NK) cells, and immunosuppressive effects of the tumor microenvironment. These issues require further investigation to achieve significant improvements. This review provides a comprehensive overview of the biological characteristics of NK cells, their antitumor mechanisms, the latest therapeutic strategies in tumor immunotherapy, and the challenges associated with NK cell-based immunotherapy, aiming to offer valuable insights for future research and clinical applications.